Three Distinct Point Mutations in the Factor IX Gene of Three Japanese CRM+ Hemophilia B Patients (Factor IX BMNagoya 2, Factor IX Nagoya 3 and 4) - Hamaguchi, Motohiro; Matsushita, Tadashi; Tanimoto, Mitsune; Tekahashi, Isao; Yamamoto, Kohji; Sugiura, Isamu; Takamatsu, Junki; Ogata, Kanji; Kamiya, Tadashi; Saito, Hidehiko (Thrombosis and Haemostasis, 1991)
Enzymatic DNA amplification and complete sequence analysis were used to investigate human factor IX coding sequences in three CRM+ hemophilia B patients. In a patient with severe hemophilia B and a markedly prolonged ox-brain prothrombin time, a C to T transition in exon VI changed the codon for Argl80 to Trp (factor IX BMNagoya 2). This mutation would impair the cleavage by factor XIa required for activation of the zymogen. In a patient with mild hemophilia B, a G to A transition in exon VI changed the codon for Argl45 to His (factor IX Nagoya 3). This substitution also would be predicted to preclude the cleavage of factor IX by factor XIa at this peptide bond (Argl45-Alal46). Furthermore, this point mutation creates a new NlaIII restriction site which provides a quick and reliable method for carrier detection in the affected family members. A patient with severe hemophilia B (factor IX Nagoya 4) had a G to A transition in exon II changing the codon for Glu21 to Lys. This novel point mutation is assumed to impair the function of factor IX by disrupting the calcium binding of factor IX.